From the Light of Rainbows: Growing the Spiralic Garden of Community-Based Inquiry and Co-Learning. - Marin, Ananda (American Indian Culture & Research Journal, 2024)
The article focuses on the transformative journey of the Indigenous Early Learning Collaborative (IELC) through Community-Based Inquiry, exploring themes of inquiry processes. Topics include the practice of asking "What's good?" as a gateway to shared abundance, the IELC's engagement in Community-Based Inquiry to strengthen Indigenous early childhood education, and the conceptualization of co-learning as a process of reflective storytelling and storylistening.